Development of Madrasah E-Magazine through Online Fliphtml5 to Improve Writing and Reading Literacy - Redite Kurniawan; Fatimatus Zahrah; Ikha Yuliati (Institut Dirosat Islamiyah Al-Amien Prenduan, 2023)
Writing and reading literacy is the key to increasing literacy in general which needs serious attention. However, special strategies are needed to increase literacy interest in the era of disruption which cannot be separated from the use of the internet and online. This research aims to develop a madrasah e-magazine to improve the literacy of madrasa residents. The method used in this study is R&D (research & development) with the ADDIE research model (analysis, design, development, implementation, and evaluation). The result of this study is an e-magazine which is published every month in the online html5 flipping magazine format. This e-magazine can be accessed from smart phones, tablets, computers, and laptops, while the rubrics in the madrasah e-magazine are filled in by students and teachers at MTs Ar-Roihan Lawang Malang in turn. Based on the results of the media expert validator, a value of 3.78 was in the good category and the value from the content validator was 4.17 in the good category. While the results of the interviews stated that 85% of students opened the madrasah e-magazine to read it. Overall the development of this madrasah e-magazine can be continued to support the madrasah literacy movement program at MTs Terpadu Ar-Roihan Lawang Malang.